A Novel Synthesis of FeO@SiO@Au@Porous SiO Structure for NIR Irradiation-Induced DOX Release and Cancer Treatment - Meng Yang; Wenhua Yang; Liang Chen; Mingjian Ding; Chenhao Li; Dongliang Shi (SAGE Publishing, 2020)
Doxorubicin (DOX) alone or in combination has been widely used for numerous cancers, including breast, lung, bladder, and so on. In this article, a core/shell/shell structured Fe 3 O 4 @SiO 2 @Au@porous SiO 2 particles for the drug delivery and release of DOX was demonstrated, with the aid of near-infrared irradiation. Fe 3 O 4 was used to direct the transportation and delivery of the drug-loaded composite to the target tissues and organs under an external magnetic field, the first layer of SiO 2 was used for Au nanoparticle attachment, Au acted as the agent for light-thermal conversion, and the porous SiO 2 was used to load DOX. The morphology of the nanoparticles was studied by transmission electron microscopy, and the porous structure was characterized by N 2 adsorption/desorption curves. The drug delivery system displayed high drug loading capacity, and the release behavior was largely impacted by the environmental pH. Furthermore, the cytotoxicity of Fe 3 O 4 @SiO 2 @Au@porous SiO 2 and DOX loaded Fe 3 O 4 @SiO 2 @Au@porous SiO 2 was studied through in vitro 3-(4,5-Dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide cell viability assay.